2022
DOI: 10.21608/asge.2022.152698.1006
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response of 2-D Plane Framed Buildings Eccentrically Braced with Vertical Shear Links

Abstract: There exist a variety of techniques which can be utilized in seismic-resistant structures in order to protect it from earthquake ground motions. One of these techniques is the employment of vertical eccentrically braced frames (V-EBFs) which dissipate energy during seismic hazard by means of yielding of certain elements, commonly referred to as vertical shear links (VSLs), whereas the whole structures is kept safe in the elastic stage. This paper presents a numerical study on 2-D framed buildings equipped with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Nevertheless, the configuration B5-6 was the only one that failed to improve the seismic performance of the building B5 despite its capability to decrease the number of the plastic hinges lying in the IO stage. This remarks an important point since the configuration B5-6 was installed with the vertical shear links specimen 12 which had the highest yield force among all other specimens, and it also had the maximum amount of dissipated energy when subjected to cyclic loading; Refer to (El-Gammal et al, 2021;Seleemah et al, 2022) for more information. The pushover curves, shown in Fig.…”
Section: Nonlinear Static Pushover Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…Nevertheless, the configuration B5-6 was the only one that failed to improve the seismic performance of the building B5 despite its capability to decrease the number of the plastic hinges lying in the IO stage. This remarks an important point since the configuration B5-6 was installed with the vertical shear links specimen 12 which had the highest yield force among all other specimens, and it also had the maximum amount of dissipated energy when subjected to cyclic loading; Refer to (El-Gammal et al, 2021;Seleemah et al, 2022) for more information. The pushover curves, shown in Fig.…”
Section: Nonlinear Static Pushover Analysismentioning
confidence: 98%
“…In addition, (Ghadami et al, 2021;Zhu et al, 2023) investigated links made of low-yield-point steel, whereas (Mirzai & Attarnejad, 2020) studied shear links made of shape memory alloys. (El-Gammal et al, 2021;Seleemah et al, 2022) showed that vertical shear links made of different metallic alloys rather than steel can be adopted in different configurations to upgrade the performance of eccentrically braced frames. In the same manner, (Mohsenian, et al, 2020) illustrated that equipping low to medium rise moment-resisting frames with vertical links can improve their overall response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation